First detection and molecular characterization of Echinococcus equinus in a Mule in Turkey - Simsek, Sami; Cevik, Aydin (De Gruyter Open Ltd, 2014)
Cystic echinococcosis is a zoonotic disease with a cosmopolital distribution. It is caused by the larval stages (metacestodes) of the parasite Echinococcus granulosus which infects different animal species. In this report, we present a case of E. granulosus infection in a mule and molecular characterization of the cyst. For this purpose parasite material was collected from the liver of a necropsied mule. DNA was isolated and PCR amplification of mitochondrial 12S rRNA as well as partial sequencing of mitochondrial cytochrome c oxidase subunit 1 (mt-CO1) genes were performed. Six unilocular cysts, filled with clear fluid were found in the liver and spleen. All cysts were found to be fertile. The 12S rRNA-PCR did not yield any band while mt-CO1-PCR yielded a 446 bp sized amplification product. Sequence corresponding to mt-CO1 gene was identical to a sequence reported for E. equinus (formerly G4) (Genbank accession number: KC953029). This is the first record of E. equinus as a cause of cystic echinococcosis in a mule in Turkey.
Keywords: Echinococcus equinus; mule; genotyping; PCR; Turkey